Healthy Patients Are Not the Best Controls for Microbiome-Based Clinical Studies: Example of Sjögren’s Syndrome in a Systematic Review - Doaré, Elise; Héry-Arnaud, Geneviève; Devauchelle-Pensec, Valérie; Alegria, Guillermo Carvajal (Frontiers in Immunology, 2021)
Introduction: It has been hypothesized that gut and oral dysbiosis may contribute to the development of primary Sjögren’s syndrome (pSS). The aim of this systematic review was to assemble available data regarding the oral and gut microbiota in pSS and to compare them to data from healthy individuals and patients with dry symptoms without a diagnosis of Sjögren’s syndrome or lupus disease to identify dysbiosis and discuss the results. Methodology: Using the PRISMA guidelines, we systematically reviewed studies that compared the oral and gut microbiota of Sjögren’s patients and controls. The PubMed database and Google Scholar were searched. Results: Eighty studies were found, and 16 studies were included: 12 referred to the oral microbiota, 3 referred to the gut microbiota, and 1 referred to both anatomical sites. The most frequent controls were healthy volunteers and patients with SICCA symptoms. The most common analysis method used was 16S-targeted metagenomics. The results were mostly heterogeneous, and the results regarding diversity were not always in accordance. Dysbiosis in pSS was not confirmed, and reduced salivary secretion seems to explain more microbial changes than the underlying disease. Conclusion: These heterogeneous results might be explained by the lack of a standardized methodology at each step of the process and highlight the need for guidelines. Our review provides evidence that SICCA patients seem to be more relevant than healthy subjects as a control group.